Implementation of Occupational Safety Standards by Public Area Attendants at Department Style Hotels in Bali - Putu Bella Anggreni; Ni Ketut Iswarini; Pitanatri, Made Uttari (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
This study aims to examine the implementation of occupational safety standards by public area attendants, Department Style Hotel X. Data collection techniques include observation, interviews, and documentation studies. Data analysis was carried out using descriptive comparative qualitative methods between high-risk occupational safety standards (High Risk Task) and their implementation by public area attendants, Department Style. The results of the study showed that full compliance (100%) in maintaining cleanliness and dryness of the floor, installing "wet floor" signs, using stairs in hard-to-reach areas, understanding the use of machines, and managing the area by two public area attendants. However, compliance with the use of masks, gloves, checking cables and machines before use, and using safety equipment was still below 100%. Factors that influence this non-compliance include haste, discomfort in using PPE (Personal Protective Equipment), and lack of inspection of the condition of the equipment.